Freedom's sword : the NAACP and the struggle against racism in America, 1909-1969 - Jonas, Gilbert (Routledge, 2005)
Freedom's Sword is the first history to detail the remarkable, lasting achievements of the NAACP's first sixty years. From its pivotal role in overturning the Jim Crow laws in the South to its twenty-year court campaign that culminated with Brown v. the Board of Education, the NAACP has been at the forefront of the struggle against American racism. Gilbert Jonas, a fifty-year veteran of the organization, tracks America's political and social landscape period by period, as the NAACP grows to 400,000 members and is recognized by both blacks and whites as the leading force for social jus.